Mãos de concreto - Wittmann, Leonardo Josef Schifino (2014)
Concrete hands, title from this dissertation, presented here as a screenplay and inserted in the Creative Writing area, is about the constant wanderings from its main character, known only as Goalkeeper . The hero, beyond trying to control his mysterious skills, seeks to reconnect with his son André. To achieve this objectives, the protagonist must overcome some obstacles, like Heitor, André s stepfather, and find a new meaning for his life after abandoning his soccer career. The narrative chooses different small towns, never named, as the main stage for the development of the plot. While some characters serve as mentors for the Goalkeeper, as his father Paul, others serve as antagonists. Besides the dissertation, there is also an essay on the screenplay s creative process, focusing on topics such as the choice for the title, the fantastic element and the importance of emotion in writing.